Biodiesel and environment protection - Owczuk, Marlena (Studia Ecologiae et Bioethicae, 2006)
The development of the automotive industry in the world causes high environmental degradation, the main source of this degradation is engine emissions. It is necessary to introduce biofuels prepared from renewable energy sources to the market due to the limited reserve of crude oil and environmental protection. Appropriate new modifications in law regulations have been prepared in European Union. Introducing alternative fuels can reduce the emissions of harmful gases and also decrease the level of pollutions in the environment.